Порівняльний аналіз застосування моделей оцінки кризового стану промислових підприємств - Соколова, Л. В.; Верясова, Г. М.; Соколов, О. Є. (ДВНЗ «Придніпровська державна академія будівництва та архітектури», 2019)
Статтю присвячено дослідженню моделей оцінки кризового стану промислових підприємств. Проведено аналіз стану вітчизняної економіки та характерних тенденцій у промисловості країни протягом останніх років. Сформовано термінологічну платформу дослідження. Складено схему покрокового алгоритму оціню- вання рівня кризового стану промислових підприємств. Розроблено узагальнену шкалу оцінки рівня кризово- го стану підприємств, що є результатом поєднання висновків за результатами процедури моделювання з наявною класифікацією криз залежно від фінансово-економічного стану підприємства. Проведено порівняль- ний аналіз застосування різних математичних моделей для оцінки рівня кризового стану підприємств за трьома промисловими кластерами: великі підприємства, середні підприємства, малі підприємства. The article highlights the study of the application of modern domestic models for assessing the crisis state of industrial enterprises that operate under unstable and dynamic external environment. As a result of analysis of earnings before incomes and taxes of three industrial clusters, namely, large, medium and small enterprises of Ukraine in terms of “proportion of loss-making enterprises”, and changes in their number in terms of “growth rate of enterprises’ quantity” during 2010-2017 we can conclude that averaging one-third of industrial enterprises are currently loss-making. Negative common tendencies of the enterprise’s activity were discovered. They don’t depend on affiliation to a particular industrial cluster. That tendencies evidence about relevance of carrying out a study on the assessment of the crisis state of business entities by means of techniques that are developed by domestic scientists. The methodology of the research is based on the developed terminology platform, the designed step-by-step algorithm of the evaluation procedure implementation, the methodical approach to com- parative assessment of the crisis state level of enterprises that refer to different types of industrial clusters. That methodology uses several domestic mathematical models for the comparative analysis implementation and gives the appropriate recommendations to model choice expediency. The generalized assessment scale is developed. It is as the result of conclusions based on the results of modeling with the existing classification of crises, depend- ing on the financial and economic state of the enterprise. The comparative analysis of the application of various mathematical models for assessing the level of crisis situation of enterprises that represent different types of industrial clusters has been carried out. Under the conditions of the fluctuation of environmental factors each in- dustrial enterprise faces with the task of permanent conduction of the procedure for assessing its level of crisis as a component of the analysis of the financial state of its activities, in order to identify and assess possible directions of sustainable development in the future.
Keywords: кризовий стан; модель оцінки; покроковий алгоритм; рівень кризового стану; crisis state; model of estimation; step-by-step algorithm; level of crisis state